ON THE NATURE OF AN UNUSUAL WAVE TRAIN OBSERVED IN THE NORTHERN TIEN SHAN REGION - Kopnichev Yu.F.; Sokolova I.N. (My University, 2004)
We describe an unusual wave group that propagates in the Northern Tien Shan region along the border between mountain ranges and the Chu and Ili depressions to the north. This wave group, which we call SL, stands out against the short-period coda on the recordings of local earthquakes and quarry explosions (at distances up to 100 km). The time tm needed for the SL group to reach maximum amplitude varies between 98 and 131 sec, and at the same time, the tm value does not depend on epicentral distance. At distances up to 30 km, the SL group has a very narrow spectrum (T = 1.5–1.8 sec), but when the epicentral distance increases, the predominant period also increases up to approximately 2.3 sec (at Δ ∼ 100 km). Characteristics of the wave group are significantly different for the Zaili fault zone than for the regions to the west of 76° E and to the east of 79° E. In the Zaili fault region, the SL group is characterized by great variability of velocity, amplitude, and polarization parameters even for nearby paths. The SL group maintains an amplitude within 0.7 of its maximum for 4–36 sec depending on the path. The polarization of the SL group is in the vertical plane in the Zaili fault-zone region and in the horizontal plane in other regions. Particle motion is elliptical or almost circular. We suggest that the SL group consists of shear waves propagating in a subvertical wave guide and reflected from a thin upper mantle layer.